A new index to evaluate exposure and potential damage to RC building structures in coastal areas. (June 2019) - Sangiorgio, Valentino; Uva, Giuseppina; Fatiguso, Fabio; Adam, Jose M.
Abstract: Exposure to an aggressive marine atmosphere can seriously harm reinforced concrete (RC) structures and affects a building's service life. In particular, buildings close to the sea are at high risk of suffering damage, mainly due to the effects of chloride. The scientific and technical communities are interested in studying new parameters related to building degradation, including "exposure to aggressive environments" in order to predict a building's service life and schedule maintenance and monitoring systems. This paper proposes a marine exposure index aimed at quantifying potential risks and damage to RC building structures. The definition of the index includes three synergistically related techniques: i) the Analytic Hierarchy Processes to analyze the complexity of the problem and the parameters involved in marine exposure; ii) a state-of-the-art technique to evaluate the degree of building degradation; iii) an optimization calibration procedure by setting a Mathematical Programming problem. The resulting index can be extensively and fruitfully applied by researchers and practitioners in order to assess the building's exposure to an aggressive marine atmosphere. Architects and engineers could apply the proposed index in any phase of the building process, from the project to the maintenance and management phases. The effectiveness of the proposal was tested in a survey of 1816 buildings on the Valencia coast (Spain). Graphical abstract: Unlabelled Image Highlights: Marine atmosphere can seriously harm reinforced concrete structures. This paper proposes a new marine exposure index. The definition of the index includes three synergistically related techniques. The index can be used to assess a building's exposure to a marine atmosphere. The index has been calibrated by surveying close to two thousand buildings.